PENGARUH SENAM YOGA TERHADAP TEKANAN DARAH LANSIA HIPERTENSI (STUDI LITERATUR REVIEW) - Nurul Hidayah (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2022)
The elderly are at high risk for degenerative diseases. One of the diseases that are often experienced by the elderly is hypertension which can disrupt blood flow, this of course can interfere with activities. One of the non-pharmacological treatments that can improve the flow of oxygen in the blood is yoga. This study was conducted to determine the effect of giving yoga exercise to lowering blood pressure in the elderly with hypertension. By using the keywords ((Yoga) AND (Hypertension) AND Elderly) in the google scholar and portal garuda databases. 6 articles were selected using JBI Critical Appraisal tools. Articles were taken from a reputable database, i.e. 1 article was taken from the garuda portal data base, while 5 articles were taken from the Google Schoolar data base. The selection was taken by taking into account the PICO framework, article 6 Test Wilcoxon Test. There is a difference in blood pressure before and after doing yoga exercises for the elderly with hypertension with a value (p value = 0.000) < from the standard significant (α = 0.05). Giving yoga exercise therapy is recommended to be done in elderly people with hypertension because there is a decrease after the action, but from several studies there are differences of opinion between one researcher and other researchers regarding the results of yoga exercise on hypertension which discuss yoga exercise is not effective for lowering blood pressure in hypertension. So that further researchers can develop non-pharmacological treatment for hypertension to lower blood pressure with other alternatives to be combined, such as using other combination therapies to be more effective in lowering blood pressure in hypertension.